PENGGUNAAN ANTIBIOTIKA BAGI PENDERITA BALITA PNEUMONIA - DAP. Rasmika Dewi; Dewa Ayu Swastini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Pneumonia is a major cause of morbidity and mortality of children under 5 years old (toddlers). The number of antibiotics use as a therapeutic treatment of pneumonia has caused bacterial resistance, medicinal side effect, and increasing medication cost. Thisresearch was carried out intended to know the relationship between antibiotic regimens used for pneumonia therapy and the outcome ofparameters, such as body temperature and respiratory rate (RR), as well as the length of stay. This study is carried out in a retrospectivedescriptive design, using pneumonia patient’s medical record (children under 5 years old), during the period from the 1December 2008. It was shown in this study that the dose of antibiotics given to pneumonia children under 5 years old are in single,combination, and transition form. The single antibiotics most widely used is Cefotaxime (87.5%), and the combination is Ampicillin–Chloramphenicol (94.4%) while transitional is Ampicillin –Chloramphenicol to Cephalosporin group (58.3%). The use of antibiotics forpneumonia among children under five patients either single, combination, and transition was successful in obtaining therapy outcome,including decreasing body temperature from > 38° C to normal body temperature, is 36° C–38° C and decreasing RR value with theaverage length of stay for five (5) days. st January – 31st